Comparison of Antimicrobial Substantivity of Six Root Canal Irrigants against Enterococcus faecalis - Palazzi, Flavio; Del Fabbro, Massimo; Taschieri, Silvio; Mohammadi, Zahed; Asgary, Saeed; Bukiet, Frédéric (Iranian Endodontic Journal, 2018)
Introduction: The antimicrobial substantivity of Mixture of Doxycycline, Citric acid, and Tween 80 (MTAD), Tetraclean, Tetraclean NA, Q-Mix, 2% Chlorhexidine (CHX) and Octenisept was assessed in human root dentine blocks infected with Enterococcus (E.) faecalis. Methods and Materials: A total of 170 dentine tubes were prepared from human maxillary incisors. After crown and apical third removal, cementum was abraded. The remaining center-holed pieces were cut into 4-mm blocks, infected with E. faecalis in Brain Heart Infusion (BHI) broth for 28 days, then randomly divided into 6 experimental groups (n=25) and 2 controls (n=10). At 0, 7, 14, 21 and 28 days, dentine chips were removed from the canals, with sequential round burs with increasing diameters, and collected into freshly prepared BHI broth. After culturing, growing colonies were counted as colony forming units (CFU). Conventional non-parametric tests (Kruskal-Wallis and Mann-Whitney tests) were used to assess intra-group (at different time frames) and inter-group (at each experimental time) differences (P=0.05). Results: Tetraclean yielded the lowest CFU counts (P<0.001) at each observation time. Tetraclean NA and Q-Mix showed better (P<0.001) substantivity than 2% CHX and MTAD (except for Q-Mix versus MTAD at 14 days, P=0.21). Conclusions: In this in vitro study, Tetraclean NA and Q-Mix displayed the best antimicrobial substantivity against E. faecalis after Tetraclean in infected human root dentine. Considering the findings of our study and potential drawbacks of antibiotic-based irrigants, free-antibiotic irrigants may represent viable alternative for final rinse in root canal treatment. Keywords: Antimicrobial Substantivity; Enterococcus faecalis; MTAD; Qmix; Tetraclean